Rapid development of visualization dashboards to enhance situation awareness of COVID-19 telehealth initiatives at a multihospital healthcare system. (3rd July 2020) - Dixit, Ram A; Hurst, Stephen; Adams, Katharine T; Boxley, Christian; Lysen-Hendershot, Kristi; Bennett, Sonita S; Booker, Ethan; Ratwani, Raj M
Abstract: The COVID-19 pandemic has led to the rapid expansion of telehealth services as healthcare organizations aim to mitigate community transmission while providing safe patient care. As technology adoption rapidly increases, operational telehealth teams must maintain awareness of critical information, such as patient volumes and wait times, patient and provider experience, and telehealth platform performance. Using a model of situation awareness as a conceptual foundation and a user-centered design approach we describe our process for rapidly developing and disseminating dashboard visualizations to support telehealth operations. We used a 5-step process to gain domain knowledge, identify user needs, identify data sources, design and develop visualizations, and iteratively refine these visualizations. Through this process we identified 3 distinct stakeholder groups and designed and developed visualization dashboards to meet their needs. Feedback from users demonstrated the dashboard's support situation awareness and informed important operational decisions. Lessons learned are shared to provide other organizations with insights from our process.